2011
DOI: 10.1029/2009jg001156
|View full text |Cite
|
Sign up to set email alerts
|

N2O seasonal distributions and air-sea exchange in UK estuaries: Implications for the tropospheric N2O source from European coastal waters

Abstract: + derived from internal resuspension and/or ammonification, or external inputs and were independent of river-borne NO 3 − . We reevaluated total UK and European estuarine N 2 O emissions using these and published data, based on an aerially weighted approach that separately identified inner and outer estuaries, and a downward revision of the total European estuarine area used in a recent synthesis. Our revised estimates, ∼1.9 ± 1.2 × 10 9 g N 2 O yr −1 for the UK and 6.8 ± 13.2 × 10 9 g N 2 O yr −1 for Europe (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
115
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 75 publications
10
115
2
Order By: Relevance
“…In contrast, the first stage of nitrification has been linked with N 2 O production (Löscher et al, 2012), making the oceans a major source of N 2 O to the atmosphere by contributing approximately 30 % (Bange et al, 2010). Estuaries such as those of the NW European shelf sea region have been shown to represent a significant source of N 2 O to the atmosphere (Barnes and Upstill-Goddard, 2011). However, results of this study indicated that open waters could not be viewed as a strong source or sink, consistent with previous observations which suggest that the open waters of shelf sea systems contribute only 0.5 % to global atmospheric N 2 O (Freing et al, 2012).…”
Section: R Clark Et Al: the Influence Of Ocean Acidification On supporting
confidence: 58%
“…In contrast, the first stage of nitrification has been linked with N 2 O production (Löscher et al, 2012), making the oceans a major source of N 2 O to the atmosphere by contributing approximately 30 % (Bange et al, 2010). Estuaries such as those of the NW European shelf sea region have been shown to represent a significant source of N 2 O to the atmosphere (Barnes and Upstill-Goddard, 2011). However, results of this study indicated that open waters could not be viewed as a strong source or sink, consistent with previous observations which suggest that the open waters of shelf sea systems contribute only 0.5 % to global atmospheric N 2 O (Freing et al, 2012).…”
Section: R Clark Et Al: the Influence Of Ocean Acidification On supporting
confidence: 58%
“…Higher divergences reached +4.5% for CO 2 solubility in cooler marine waters, +5.65% for CH 4 solubility in warmer saltier waters, and −2.1% for N 2 O solubility in brackish waters. Hence, the algorithms diverge by as much as 0.045 mol·mol −1 of CO 2 , 0.0015 mol·mol −1 of CH 4 and 0.012 mol·mol −1 of N 2 O (i.e., mol of gas in the ocean surface per mol of gas in the atmosphere) in some of the most sensitive situations for Earth System Modelling and satellite data processing, namely: (i) the cooler marine sub-polar waters where the solubility pump traps greenhouse gases and carries them to the deep ocean [2], and (ii) the warmer waters at the coastal ocean and seas, which have regularly been observed having greenhouse gases and DMS dissolved in concentrations highly unbalanced with those of the atmosphere [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Solubility Estimatesmentioning
confidence: 99%
“…On the other hand, at the surface of coastal waters the balances and fluxes of CO 2 , CH 4 , N 2 O and DMS are very heterogenic, mostly due to factors like upwelling, plankton productivity, and land-originated loads of both natural and anthropogenic cause. Consequently, besides DMS [3,4] the coastal ocean can be, at least seasonally, also a source of CO 2 [1,2,[5][6][7][8][9][10][11], CH 4 [2,10,12], and N 2 O [2,10,[13][14][15] to the atmosphere. Thus, the uncertainty on the atmosphere-coastal ocean exchange of CO 2 begs the question about the overall budget of the global ocean [1,3,6,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrification and denitrification often occur simultaneously in aquatic ecosystems and their relative contribution to total N 2 O production is difficult to disentangle. As nitrification is an aerobic process in well-oxygenated estuarine systems, the water column mostly contributes N 2 O through nitrification production (de Wilde and de Bie 2000, Barnes and Upstill-Goddard 2011). Denitrification is usually limited to zones under hypoxic conditions (DO <2 ml L -1 ), although some denitrification may occur even in relatively oxygenated waters (de Bie et al 2002).…”
Section: Introductionmentioning
confidence: 99%